Pengembangan Media Kadobudi (Kartu Domino Budaya Indonesia) pada Materi Kebudayaan Indonesia Siswa Kelas IV Sekolah Dasar - Urmila Sheba Nedianna; Erwin Putera Permana; Farida Nurlaila Zunaidah (Departement of Mathematics Education, 2023)
The objectives achieved in this study are to find1) the feasibility of Kadobudi media in social studies learning content on Indonesian cultural diversity in class IV students. 2) the practicality of Kadobudi media in social studies learning content on Indonesian cultural diversity in grade IV students. 3) the effectiveness of Kadobudi media on social studies learning content on Indonesian cultural diversity in grade IV students. This study uses research and development R&D methods using the ADDIE model, there are 5 namely analysis, design, development, implementation, and evaluation. The subjects of this study were fourth grade students at SDN Mojoroto 4, Kediri City. The research data collection instruments were observation and interviews. The research was carried out using data analysis techniques in the form of media and material validation questionnaires, posttest questions, teacher and student response questionnaires. The results of this study are (1) The results of this study indicate that the Kadobudi media is declared valid, it can be proven by the validation results of media experts obtaining a score of 85.4%, on the validation results of IPS material experts obtaining a score of 96%. So, the average percentage score obtained from media and material experts is 90.7% with very valid criteria. (2) The results of this study indicate that the Kadobudi media is stated to be practical, it can be proven by the results of the teacher's response questionnaire obtaining a score of 93.8%, on the results of the student response questionnaire obtaining a score of 95%. So, the average percentage score obtained from the teacher and student response questionnaire is 94.4% with very practical criteria. (3) The results of this study indicate that the Kadobudi media is declared effective, it can be proven by the results of the posttest scores obtaining an average score of 86.25% by obtaining 90% mastery of classical learning included in the very effective criteria. Based on the conclusions of the results of this study, it can be stated that the Kadobudi learning media is declared valid, practical and effective.